Religious Identity Politics and the Challenges of Democracy in Indonesia: A Study of Banjar People’s Fanaticism toward Ulama - Syifa, Dian May; Zulfaidah, Rena; Abdillah, Muhammad Torieq; Mustofa, Ainul (Suhuf: International Journal of Islamic Studies, 2026)
Background: The growing use of religion in political contestation in Indonesia highlights the rise of religious identity politics, particularly in highly religious communities such as the Banjar people, where strong reverence toward ulama influences political behaviour and democratic dynamics. Objective: This study aims to analyze the construction of religious identity politics, the role of ulama’s charismatic authority, and its implications for the sustainability of democracy in Indonesia. Methodology: This research employs a qualitative design through a systematic literature review, supported by conceptual, thematic, and normative analysis. The study integrates theories of identity politics, Barth’s boundary-making, and Weber’s charismatic authority to interpret socio-political phenomena. Results: The findings indicate that the strong legitimacy and influence of ulama in Banjar society facilitate identity-based political mobilization. While this can increase political participation and solidarity, it also contributes to polarisation, intolerance, and the decline of rational public discourse. Conclusion: Religious identity politics, when driven by charismatic authority, presents both opportunities and challenges for democracy, potentially strengthening cohesion while risking democratic quality.